Bhopal's ecological gothic : disaster, precarity, and the biopolitical uncanny - Nayar, Pramod K. (Ecocritical theory and practice., 2017)
Studies the cultural texts--fiction, protest effigies, photographs, films, reportage, eyewitness accounts, campaign posters and reports--produced around the world's worst industrial disaster: the Bhopal tragedy of 1984. It makes a case for an ecological perspective, wherein the city, its landscape and its people are Gothicized. After presenting the history of the disaster in terms of negligence, the book examines the coverage of the events as well as accounts by eyewitnesses and survivors, and the remnants, in various forms, of the disaster - the haunting - within human bodies and nature. Finally,Bhopal's Ecological Gothic describes the industrial ruins and the mobilization of protests against Union Carbide. -- Back cover.